Literatur Review : Faktor Kondisi Lingkungan dengan Kejadian Leptospirosis - Khaira Ilma; Martini Martini; Mursid Raharjo (Jurnal Serambi Engineering, 2023)
AbstrakLeptospirosis is a zoonotic infectious disease caused by Leptospira bacteria, characterized by acute fever in humans where infection occurs due to direct or indirect contact with the urine of animals that have been infected with the bacteria. There were 906 cases of leptospirosis that occurred in Indonesia in 2020. This study aims to provide some overview information about the environmental conditions in which leptospirosis has been studied in Indonesia. This study uses a review study method by identifying, recording and analyzing research that has been previously studied from 10 scientific articles related to the incidence of leptospirosis. The results of the research based on a review study of several articles that have been carried out found several factors of environmental conditions for the occurrence of leptospirosis, including the condition of the gutters, the presence of rats, the presence of rice fields and the presence of a river from the case house, age, gender, occupation, landfills, puddles, pets.Keywords: factors, conditions, environment, leptospirosis, events